PEREMPUAN DALAM POLITIK: MODALITAS KEMENANGAN PADA PEMILIHAN KEPALA DESA PADANG BARU TAHUN 2022 - Putri Adella; Bahjatul Murtasidin; Ranto Ranto (LPPM Universitas Abdurrab, 2023)
Democratic values are contained in the implementation of general elections in which general elections become a forum for citizens to participate in political activities, whether elected or elected without any gender limitations. However, throughout history, women have been a minority group in the political arena because of the assumption that political culture was made specifically for men, so that women who enter politics are seen as going against their nature in the domestic world. To minimize gender bias in policy making in politics, it is necessary to represent women in the smallest units such as village government. This study uses a qualitative research method that uses in-depth analysis with data collection techniques, namely interviews, field notes, drawings, photographs, video recordings and others. In this study it was found that Amnah's victory as the first woman to win the regional election was based on social capital which dominated her political strategy game. By taking advantage of the trust from the community and providing real action in building physical resources that benefit the village, a name recognition is created for her that makes her win the election of village head. In this case Amnah fought against several male candidates in which the candidates' fight lay in the game of economic capital in the form of political transactions involving the candidates and the community. Apart from that, it is a game of symbolic capital (identity) which is used to gain votes or support from certain groups. It was this modality and strategy that made Amnah the winner in the 2022 Election of Padang Baru Village Head.